The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3847/2041-8213/ab5c27
|View full text |Cite
|
Sign up to set email alerts
|

Candidate Hypervelocity Red Clump Stars in the Galactic Bulge Found Using the VVV and Gaia Surveys*

Abstract: We propose a new way to search for hypervelocity stars in the Galactic bulge, by using red clump (RC) giants, that are good distance indicators. The 2nd Gaia Data Release and the near-IR data from the VISTA Variables in the Via Lactea (VVV) Survey led to the selection of a volume limited sample of 34 bulge RC stars. A search in this combined data set leads to the discovery of seven candidate hypervelocity red clump stars in the Milky Way bulge. Based on this search we estimate the total production rate of hype… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 58 publications
0
24
2
Order By: Relevance
“…Some other mechanisms of generating HVSs have been proposed, including the interactions between a star and the binary black hole at the center (Yu & Tremaine 2003), the interactions between binary stars and binary black holes , the interactions between the MW and a dwarf galaxy (Abadi et al 2009), and star formation in the outflows driven by an active galactic nucleus (Wang & Loeb 2018;Silk et al 2012). Since the serendipitous discovery of the first HVS (Brown et al 2005), ∼90 high-velocity stars have been identified as candidate HVSs (see, e.g., Hirsch et al 2005;Edelmann et al 2005;Brown et al 2006Brown et al , 2009Brown et al , 2012Brown et al , 2014Brown et al , 2018Tillich et al 2011;Li et al 2012Li et al , 2015Li et al , 2021Pereira et al 2013;Zheng et al 2014;Huang et al 2017;Marchetti et al 2017;Neugent et al 2018;Massey et al 2018;Hattori et al 2018a;Erkal et al 2019;Du et al 2019;Luna et al 2019;Koposov et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Some other mechanisms of generating HVSs have been proposed, including the interactions between a star and the binary black hole at the center (Yu & Tremaine 2003), the interactions between binary stars and binary black holes , the interactions between the MW and a dwarf galaxy (Abadi et al 2009), and star formation in the outflows driven by an active galactic nucleus (Wang & Loeb 2018;Silk et al 2012). Since the serendipitous discovery of the first HVS (Brown et al 2005), ∼90 high-velocity stars have been identified as candidate HVSs (see, e.g., Hirsch et al 2005;Edelmann et al 2005;Brown et al 2006Brown et al , 2009Brown et al , 2012Brown et al , 2014Brown et al , 2018Tillich et al 2011;Li et al 2012Li et al , 2015Li et al , 2021Pereira et al 2013;Zheng et al 2014;Huang et al 2017;Marchetti et al 2017;Neugent et al 2018;Massey et al 2018;Hattori et al 2018a;Erkal et al 2019;Du et al 2019;Luna et al 2019;Koposov et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, our knowledge on the kinematics of Milky Way stars both fast and slow has been revolutionized by the European Space Agency's ongoing Gaia mission (Gaia Collaboration et al 2016bCollaboration et al , 2018Collaboration et al , 2021a. With unprecedented astrometric measurements of ∼2 billion Galactic sources and radial velocity measurements for a subset of ∼millions of cool, bright stars, Gaia has demystified the origins of some HVS candidates (Irrgang et al 2018;Brown et al 2018;Erkal et al 2019;Kreuzer et al 2020) recategorized others as spurious detections and/or bound stars (Boubert et al 2018(Boubert et al , 2019Marchetti 2021), and discovered new (candidate) stars with extreme velocities (Bromley et al 2018;Shen et al 2018;Hattori et al 2018;Du et al 2019;Luna et al 2019;Marchetti et al 2019;Li et al 2021;Marchetti 2021). While these unbound star candidates are each fascinating in their own right, it is conspicuous that promising genuine HVS candidates, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…On the observational side, it was W. R. Brown who serendipitously discovered the first HVS candidate: a B-type star escaping the MW with a galactocentric velocity of ∼700 km s −1 (Brown et al 2005). Many HVS candidates were later found in both targeted and un-targeted surveys (e.g., Hirsch et al 2005;Edelmann et al 2005;Brown et al 2006aBrown et al ,b, 2007aBrown et al ,b, 2009Brown et al , 2012Brown et al , 2014Tillich et al 2011;Li et al 2012Li et al , 2015Li et al , 2021Pereira et al 2013;Zheng et al 2014;Huang et al 2017;Neugent et al 2018;Du et al 2019;Luna et al 2019;Koposov et al 2020). Some of these observed stars have speeds lower than the Galactic escape velocity: they are referred to as "bound HVSs".…”
Section: Introductionmentioning
confidence: 99%